KOMPETENSI RELATIF PADA PENGADILAN HUBUNGAN INDUSTRIAL TERHADAP PERSELISIHAN PEMUTUSAN HUBUNGAN KERJA (STUDI PUTUSAN NOMOR 106/PDT.SUS-PHI/2019/PN.PBR): Relative Competence at the Industrial Relations Court Regarding Termination of Employment Disputes (Study of Decision Number 106/Pdt.Sus-PHI/2019/Pn.Pbr) - Arya Falah Al Multazam; Yogo Pamungkas (Faculty of Law, Universitas Trisakti, 2025)
Workers or labor unions related to issues related to employment relations. The purpose study was to determine the judge's considerations in deciding the dispute between Widodo Mulyadi and PT Antar Mitra Sembada Pekanbaru Branch Office in accordance with Law Number 2 of 2004 and to determine the decision Pekanbaru Industrial Relations Court Judge in examining and deciding the dispute over Termination Employment by PT Antar Mitra Sembada against Widodo Mulyadi in accordance with Laws and Regulations. The writing method uses normative studies. The conclusion drawn is that in Decision Number 106 / Pdt.Sus-PHI / 2019 / PN.Pbr based on evidence and facts during trial which proves that the Plaintiff is indeed an employee defendant, where in his last placement as Sales Coordinator Combo Semarang after Defendant submitted a demotion letter. In this case, Pekanbaru Industrial Relations Court should accept Defendant's Exception regarding Relative Competence. The decision Pekanbaru Industrial Relations Court Judge is not in accordance with Law Number 2 of 2004 concerning Settlement Industrial Relations Disputes, namely Article 81 concerning Relative Competence, which in final placementPlaintiff as Sales Coordinator Combo Semarang after Defendant submitted demotion letter and was registered as an employee of PT. Antarmitra Sembada Semarang Branch.